2011
DOI: 10.1073/pnas.1111691108
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Newcastle disease virus hemagglutinin-neuraminidase (HN) ectodomain reveals a four-helix bundle stalk

Abstract: The paramyxovirus hemagglutinin-neuraminidase (HN) protein plays multiple roles in viral entry and egress, including binding to sialic acid receptors, activating the fusion (F) protein to activate membrane fusion and viral entry, and cleaving sialic acid from carbohydrate chains. HN is an oligomeric integral membrane protein consisting of an N-terminal transmembrane domain, a stalk region, and an enzymatically active neuraminidase (NA) domain. Structures of the HN NA domains have been solved previously; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
272
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(291 citation statements)
references
References 36 publications
18
272
1
Order By: Relevance
“…The virus increased neuraminidase activity to promote virus release when its hemagglutinin ability was improved. In the same mutant, the impact on receptor-binding ability, neuraminidase activity, and cell fusion is different (36). The mutations in NDV HN demonstrated that R174L, R416L, R498L, E547Q, Y526L, and I175E impacted the receptor binding ability and NA activity.…”
Section: Discussionmentioning
confidence: 99%
“…The virus increased neuraminidase activity to promote virus release when its hemagglutinin ability was improved. In the same mutant, the impact on receptor-binding ability, neuraminidase activity, and cell fusion is different (36). The mutations in NDV HN demonstrated that R174L, R416L, R498L, E547Q, Y526L, and I175E impacted the receptor binding ability and NA activity.…”
Section: Discussionmentioning
confidence: 99%
“…The stalk domain structures of NDV (63) and PIV5 (64) have recently been solved, and our chimeric proteins were modeled based on the NDV structure (Fig. 16).…”
Section: Discussionmentioning
confidence: 99%
“…4). Together with biochemical and structural data of paramyxovirus attachment proteins (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), a general model of paramyxovirus fusion has been proposed: upon activation by the attachment protein, metastable prefusion F undergoes a series of large-scale, ATP-independent conformational changes, going down an energy gradient from a metastable prefusion state to a highly stable postfusion state. The energy released during F refolding is believed to facilitate membrane fusion to create a pore between the virus and host cell through which the viral ribonucleoprotein complex can enter the target cell.…”
mentioning
confidence: 99%